2004
DOI: 10.1001/archinte.164.14.1546
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid Level as a Risk Factor for Cardiovascular and All-Cause Mortality in Middle-aged Men

Abstract: Serum uric acid levels are a strong predictor of cardiovascular disease mortality in healthy middle-aged men, independent of variables commonly associated with gout or the metabolic syndrome. Serum uric acid measurement is an easily available and inexpensive risk marker, but whether its relationship to cardiovascular events is circumstantial or causal remains to be answered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
265
0
26

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 602 publications
(306 citation statements)
references
References 49 publications
15
265
0
26
Order By: Relevance
“…It has also been indicated that in 4 seasons of the annual training cycle (adopted from Bompa, 1999), the match season in which the training moved towards anaerobic, the relaxing activity of this enzyme was high, and this is consistent with the findings of the present study because HIIT activities in which the major energy system is anaerobic can increase this enzyme and as a result, improve the salvage pathway purine nucleotides (26). One of the considerable findings of the present study is the significant increase in hypoxanthine, which indicates breakdown of ATP, and also lower serum uric acid, which is an indicator of inflammation and injury, suggesting that although uric acid is the final product of purine in humans, in this study it not only did not increase, but also decreased (27). An overall look at the research may suggest that exercise stress caused excretion of purine nucleotide and high energy metabolism.…”
Section: Discussionsupporting
confidence: 41%
“…It has also been indicated that in 4 seasons of the annual training cycle (adopted from Bompa, 1999), the match season in which the training moved towards anaerobic, the relaxing activity of this enzyme was high, and this is consistent with the findings of the present study because HIIT activities in which the major energy system is anaerobic can increase this enzyme and as a result, improve the salvage pathway purine nucleotides (26). One of the considerable findings of the present study is the significant increase in hypoxanthine, which indicates breakdown of ATP, and also lower serum uric acid, which is an indicator of inflammation and injury, suggesting that although uric acid is the final product of purine in humans, in this study it not only did not increase, but also decreased (27). An overall look at the research may suggest that exercise stress caused excretion of purine nucleotide and high energy metabolism.…”
Section: Discussionsupporting
confidence: 41%
“…Our study did not aim to assess the relationship between the change of SUA and mortality risks. A single measurement of SUA to predict outcomes was a simplified and practical approach, similar to what was done by previous researchers 5, 6, 7, 8, 10, 11. Information on diuretics and urate‐lowering agents was lacking in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Uric acid, the final product of purine degradation in humans, mediates proinflammatory endothelial dysfunction and is associated with greater risks for CVD events 3, 4. Although a wealth of research has reported that an elevated serum uric acid (SUA) level >7 mg/dL independently predicts all‐cause and CVD‐related mortality in middle‐aged adults,5, 6, 7 studies linking hyperuricemia to mortality risks in the elderly population are conflicting and inconclusive 8, 9, 10, 11, 12, 13, 14. Earlier studies indicate that hyperuricemia is associated with increased risks of death from any causes and CVD‐related mortality in older adults 8, 9, 10, 11.…”
mentioning
confidence: 99%
“…Elevated SUA levels have been shown to be associated with atherosclerosis [3] and risk factors for CAD such as hypertension [4], obesity [5], diabetes [6], metabolic syndrome [7,8] and chronic renal failure [9,10,11]. Several studies in healthy subjects [12,13,14] and CAD patients [15,16,17,18,19,20,21] have shown that elevated SUA levels independently predict worse cardiovascular outcomes, while the Framingham study [22] and others [23,24,25] failed to support these findings. Although it is well known that SUA levels are partially influenced by renal function [26], the relationship between the cardiovascular risk associated with hyperuricemia and renal dysfunction has not been previously investigated.…”
Section: Introductionmentioning
confidence: 99%